Pengaruh Metode Pembelajaran Index Card Match Untuk Meningkatkan Hasil Belajar PPKn Siswa Kelas VI SD - Lestari, Nurita Aulia; Anggraeni Dewi, Dinie; Mulyana, Agus (Prodi Pendidikan IPS, Universitas Tanjungpura, 2023)
This research is motivated by the learning process which is still monotonous or only uses the lecture method and the lack of variations in learning so that students become less active in the learning process. The learning method used is quasi-experimental with a quantitative approach and one group pretest-posttest design which in its implementation only involves one class as an experimental class without any comparison class (control class). The purpose of this study was to determine the effect of the index card match type cooperative learning method on the learning outcomes of PPKn students of grade VI SD. Hypothesis testing was carried out with the Wilcoxon non-parametric test. Based on the results of the paired sample difference test using the Wilcoxon test with the help of SPSS, a p value of 0.000 (p <0.05) was obtained, which means that H₀ is rejected and Ha is accepted, which means that there is a significant difference in the average pretest and posttest scores. on students, or interpreted as treatment of students is proven to be able to increase student scores.